Role of fluorine surface modification in improving electrochemical cyclability of concentration gradient Li[Ni0.73Co0.12Mn0.15]O2 cathode material for Li-ion batteries. Issue 31 (10th March 2016) - Wang, Jingpeng; Du, Chunyu; Yan, Chunqiu; Xu, Xing; He, Xiaoshu; Yin, Geping; Zuo, Pengjian; Cheng, Xinqun; Ma, Yulin; Gao, Yunzhi
Abstract : The fluorine-modified Li[Ni0.73 Co0.12 Mn0.15 ]O2− x F x materials exhibit superior cycling stability, which is attributed to the synergistic protection of the surface NiO-like phase and fluoride layer. Abstract : This paper reports the surface fluorine modification of the nickel-rich concentration gradient Li[Ni0.73 Co0.12 Mn0.15 ]O2 material by facile high temperature annealing, and its influence on the electrochemical performance. The samples are characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, galvanostatic charge–discharge behaviour and electrochemical impedance spectroscopy. It is found that the fluorine surface modification induces a partial phase transformation from a layered structure to a cubic rock structure (NiO-like phase) on the surface region. Meanwhile, the lithium residues on the surface of the pristine material are remarkably reduced and transformed into fluorides after the fluorine modification. The fluorine-modified concentration gradient Li[Ni0.73 Co0.12 Mn0.15 ]O2− x F x ( x = 0.02) material exhibits a remarkably enhanced capacity retention of 97.5% after 200 cycles, which is significantly higher than that of the pristine material (87.4%). The superior electrochemical stability of the fluorine-modified Li[Ni0.73 Co0.12 Mn0.15 ]O2− x F x samples is attributed to the synergistic protection of the NiO-like phase and the surface fluoride layer, which can effectively restrain the side reactions between the active material and electrolyte. The fluorine-modified concentration gradient Li[Ni0.73 Co0.12 Mn0.15 ]O2− x F x materials present a promising type of cathode material for lithium-ion batteries.